PENERAPAN PERMAINAN KARTU KATA UNTUK MENINGKATKAN KEMAMPUAN MEMBACA SISWA KELAS 2 MI MA’ARIF PAGEDONGAN TENGAH - Hasanah, Nifa Nur; Fathkhurrahman, Fathkhurrahman; Fatiatun, Fatiatun; Masruroh, Dwi (Pendidikan Agama Islam (S2), UNSIQ Wonosobo, Jawa Tengah, 2023)
This study aims to: 1) To determine the implementation of the application of word card games for class 2 students of MI Ma'arif Pagedongan Tengah in the 2022/2023 Academic Year; 2) To determine the improvement in reading ability after the application of the word card game method to class 2 students of MI Ma'arif Pagedongan Tengah in the 2022/2023 Academic Year. The results of this study indicate that the application of the word card game method has a positive impact on 1) The reading ability of class 2 MI Ma'arif Pagedongan Tengah in implementing learning has improved. Marked by the completion of student learning activities in each cycle, namely in the Pre-Cycle the completion only reached 20%, in Cycle I it reached 35% and in Cycle II it increased to 90%; 2) Increase in the average value of students' reading skills. The average value of students' reading skills in the Pre-Cycle was 49.75 with the criteria